Scrutinizing Financial Accounting of Bank Ratio and Macroeconomics Influence on Economic Volatility in Indonesia - Lakilaki, Eogenie; Muhamad Zaky Ramadhan; Mafazah; Panca Wijaya (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
This study delves into the complex dynamics between interest rates, capital adequacy (CAR), liquidity (LDR), inflation, and GDP on working capital lending in Indonesia from 2017 to 2024. Amid growing macroeconomic uncertainties, the research addresses critical gaps in the understanding of how banking institutions adjust to both inherent structural resilience and external economic shocks. By incorporating Positive Accounting Theory (PAT), this paper provides a nuanced perspective on the managerial decision-making process, focusing on how regulatory frameworks and incentive structures influence credit allocation. Utilizing panel data from 102 commercial banks and employing a multiple linear regression model, the study reveals that interest rates significantly impede lending activities, whereas CAR, LDR, and GDP growth exert a robust and positive impact on credit disbursement. Conversely, inflation demonstrates a negative yet statistically insignificant effect. These findings underscore the dual role of financial stability and macroeconomic growth in facilitating efficient credit intermediation. The study calls for the development of policy frameworks that align monetary governance with institutional behaviors, advancing the broader constitutional objectives of public welfare and social justice, as enshrined in Indonesia’s constitution.